Digital Motherhood - Nariman Sawalha; Veronika Karnowski (European Journal of Health Communication (EJHC), 2022)
Smartphone apps for self-tracking breastfeeding emerged as a popular tool among new mothers. Yet, we know little about how mothers use these apps and, most importantly, how self-tracking breastfeeding relates to maternal well-being. After surveying a sample of German mothers engaging with breastfeeding trackers (n = 234; recruited via an online access panel), we identified three types of self-tracking usage: (1) straightforward basic trackers, (2) meticulous data collectors, and (3) advisory-oriented self-trackers. These usage types differ regarding the data they register, the algorithmic feedback they retrieve, and their conversational levels about parameters tracked. Our findings suggest that overall maternal well-being – in terms of confidence, stress, and self-worth – remains largely unaffected by different self-tracking usage. However, when considering only the mothers’ confidence concerning breastfeeding, breastfeeding self-efficacy is lower among those most engaged in tracking and higher among those least engaged with it. Implications of these findings are discussed in terms of whether breastfeeding trackers enhance or undermine mothers’ confidence in their breastfeeding abilities relative to the intensity of their self-tracking use. Thus, future research may include longitudinal designs to validate these findings and derive effective app-supported smartphone interventions for breastfeeding mothers.